PREVALENSI BAKTERI COLIFORM DAN Escherichia coli PADA DAGING SAPI YANG DIJUAL DI PASAR TRADISIONAL DAN PASAR MODERN DI KOTA PEKANBARU - Jasmadi '; Yuli Haryani; Christine Jose (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Beef is potential as a medium for microbial growth such as coliform bacteria since it has a high nutrients content. Coliform bacteria in a given amount could be used as a hygienic indicator and a sign for the presence of pathogenic bacteria. One species of coliform bacteria that often contaminate meat is Escherichia coli. Escherichia coli is a normal flora in gastrointestinal tract, but some strains of them are pathogens which cause acute diarrhea. The aim of this study was to calculate the number of coliformbacteria and to detect the presence of Escherichia coli in beef sold in traditional and modern markets in Pekanbaru using the Most Probable Number method. The results showed that all samples were found to be contaminated by Escherichia coli andcoliform bacteria. The number of coliform bacteria in all samples exceeded the maximum threshold of bacterial contamination according to Indonesian National Standard No. 7388:2009, i.e 1x102 MPN/g. The number of coliform bacteria in samplessold at traditional and modern markets were in the range of 0.11 x10 7 MPN/g to >24x10 7 MPN/g and 0.35 x10 8 MPN/g to >24x10 8 MPN/g, respectively.